Research on agricultural technology gap between China and Africa and its optimization path: based on meta-frontier SBM and fsQCA - Lin, Qingning; Wang, Jingyi; Mao, Shiping; Li, Jingdong (Frontiers in Sustainable Food Systems, 2023)
Recently, COVID-19 pandemic, locust plague, drought and conflict have seriously affected the development of agriculture in Africa, which make Africa countries difficultly to achieve the Sustainable Development Goals (SDGs) 1 and 2. As the cornerstone of agricultural development, technological progress has made brilliant contributions to achieving food security and nutrition improvement in African countries. And as the largest economic and trade partner of Africa, analyzing the agricultural technology gap between China and African countries and exploring optimal paths also has great significance for achieving SDGs 8 and 9. Therefore, the paper used the Meta-frontier SBM model to measure the agricultural technology gap between China and African countries from 2003 to 2019, and explores sources of the gap. On this basis, 24 African countries were taken as samples to identify multiple paths for narrowing the technology gap between China and Africa with the help of the configuration analysis method of the fuzzy-set qualitative comparative analysis (fsQCA). The results showed that the overall agricultural technology gap between China and Africa was narrowing, which was mainly caused by the reduction of pure technical inefficiency. However, sources of technology gap in African countries with different economic development levels were different. Configuration analysis found that agricultural technology innovation and institutional environment were the key conditional variables to narrow the agricultural technology gap between China and Africa. Five paths had been formed around two key conditional variables, and further summarized into three driving modes: “technology-environment” driving mode, “technology-organization” driving mode and “organization-environment” driving mode. Furthermore, this paper explored the multiple concurrent causality of narrowing the technology gap, which overcomes the deficiency of using regression methods. The paper highlights the importance of enhancing the integration of technical, organizational, and environmental conditions in African countries to collectively advance agricultural scientific and technological progress